Loss of GABA co-transmission from cholinergic neurons impairs behaviors related to hippocampal, striatal, and medial prefrontal cortex functions - Goral, R. Oliver; Harper, Kathryn M.; Bernstein, Briana J.; Fry, Sydney A.; Lamb, Patricia W.; Moy, Sheryl S.; Cushman, Jesse D.; Yakel, Jerrel L. (Frontiers in Behavioral Neuroscience, 2022)
Altered signaling or function of acetylcholine (ACh) has been reported in various neurological diseases, including Alzheimer’s disease, Tourette syndrome, epilepsy among others. Many neurons that release ACh also co-transmit the neurotransmitter gamma-aminobutyrate (GABA) at synapses in the hippocampus, striatum, substantia nigra, and medial prefrontal cortex (mPFC). Although ACh transmission is crucial for higher brain functions such as learning and memory, the role of co-transmitted GABA from ACh neurons in brain function remains unknown. Thus, the overarching goal of this study was to investigate how a systemic loss of GABA co-transmission from ACh neurons affected the behavioral performance of mice. To do this, we used a conditional knock-out mouse of the vesicular GABA transporter (vGAT) crossed with the ChAT-Cre driver line to selectively ablate GABA co-transmission at ACh synapses. In a comprehensive series of standardized behavioral assays, we compared Cre-negative control mice with Cre-positive vGAT knock-out mice of both sexes. Loss of GABA co-transmission from ACh neurons did not disrupt the animal’s sociability, motor skills or sensation. However, in the absence of GABA co-transmission, we found significant alterations in social, spatial and fear memory as well as a reduced reliance on striatum-dependent response strategies in a T-maze. In addition, male CKO mice showed increased locomotion. Taken together, the loss of GABA co-transmission leads to deficits in higher brain functions and behaviors. Therefore, we propose that ACh/GABA co-transmission modulates neural circuitry involved in the affected behaviors.